Requirement for cystatin C testing in chronic kidney disease: a retrospective population-based study - Lasserson, D; Shine, B; O'Callaghan, C; James, T (Royal College of General Practitioners, 2017)
Creatinine-based estimated glomerular filtration rate (eGFR) determines chronic kidney disease (CKD) stage, but underestimates renal function. The 2014 updated guidance from the National Institute for Health and Care Excellence (NICE) recommends that GPs reduce overdiagnosis of CKD stage 3a (eGFR 45-60 ml/min/1.73 m2) by using the renal biomarker cystatin C.To determine the population requirement for cystatin C testing, compared with current national availability of the assay.Retrospective study of primary care laboratory requests in Oxfordshire, England.The first creatinine results from tests ordered in primary care over a 6-year period (2008-2014) in a population of 600 000 in Oxfordshire were analysed and the number of patients with CKD stage 3a without proteinuria (who, in accordance with NICE guidance, required cystatin C) was determined. A conservative estimate of the national need was provided by scaling the population of Oxfordshire to the national population (CKD prevalence in the county is below the national average). Cystatin C assay availability was determined using national databases of laboratory assay provision.From a population of 600 000, there were 22 240 individuals with stable stage 3a CKD and no proteinuria. As the population of Oxfordshire equates to 1% of the UK population, there is an initial requirement for at least 2 million people to have their CKD status determined with cystatin C testing. Eight laboratories (2.1% of UK laboratories) reported cystatin C assay provision.There is a substantial gap between cystatin C assay requirements in primary care and national assay provision. This is a major barrier to implementing NICE guidance.